Reconstructive hip surgery in children with cerebral palsy: factors influencing risk of femoral head avascular necrosis. Issue 2 (March 2022) - Minaie, Arya; Smythe, Margaret; Gordon, Joe Eric; Schoenecker, Perry; Hosseinzadeh, Pooya
Abstract : Femoral head avascular necrosis (AVN) is a complication of hip reconstruction in children with cerebral palsy (CP) with uncertain incidence. The purpose of this study was to establish the rate of AVN in children undergoing hip reconstruction and to identify the factors associated with AVN. Medical records and radiographs of patients aged 1-18 with a diagnosis of CP who have undergone hip reconstruction over a 9-year period (2010–2018) with at least 1-year follow-up were reviewed. Age at time of surgery, sex, Gross Motor Function Classification System (GMFCS), procedure(s), preoperative migration percentage (MP), and signs of AVN on anterioposterior pelvis radiographs at routine follow-up visits (3 months, 6 months, and years 1–9, annually) according to the Bucholz–Ogden (BO) and Kalamchi–MacEwen (KM) classification systems were recorded. Univariate analysis was used to test for significance. Three hundred forty-nine hips in 209 patients met our inclusion criteria. Eleven hips (rate; 3%), in 11 patients, developed AVN. Classification of AVN was found to consist of: class I-4 (36%), class II-1 (9%), class III-[BO: 4 (36%)] [KM: 3 (27%)], and Class IV-[BO: 2 (18%)] [KM: 3 (27%)]. Average follow-up was of 3.5 years. The AVN cohort displayed older age (11.0 ± 2.8 vs. 8.1 ± 3.4; P = 0.005). Open reduction was associated with increased AVN, occurring in 9% of the hips ( P = 0.004). No significant association was found between preoperative MP, GMFCS, or acetabular osteotomy. The method of open reduction (anterior vs. medial) was not significantly associated with AVN ( P = 0.4471). In this large series, the observed rate of AVN was 3%, associated with open reductions at time of hip reconstruction. If possible, closed reduction would be preferred at time of hip reconstruction in children with CP to lower the risk of AVN. Level of evidence: III.